Timing matters: A meta-analysis on the dynamic effect of stress on salivary immunoglobulin - Seizer, Lennart; Stasielowicz, Lukasz; Löchner, Johanna (Brain Behavior and Immunity, 2024)
The impact of psychological stress on physiological systems has been a focus of extensive research, particularly in understanding its diverse effects on immune system activity and disease risk. This meta-analysis explores the dynamic effect of acute stress on salivary immunoglobulin-A (S-IgA) levels, a key biomarker for secretory immunity within the oral environment. Analyzing data from 34 samples comprising 87 effect sizes and a total of 1,025 subjects, a multi-level approach is employed to account for the temporal variability in measuring the stress response. The results reveal a significant increase in S-IgA levels peaking around 10 min after stress exposure, followed by a return to baseline levels approximately 30 min later. In addition, the meta-analysis identified several research gaps of the extant literature, such as limitations in the considered time lag after stress. In conclusion, the findings emphasize the temporal nuances of the S-IgA response to stress, which can help to infer potential biological pathways and guide sampling designs in future studies. Further, we highlight the use of a multi-level meta-analysis approach to investigate the temporal dependencies of the interplay between stress and immune functioning.
CRIS-Team Scopus Importer:2024-11-26
Keywords: Adaptive immunity; B-cell; Psychoneuroimmunology; Saliva; Stress